Case Report: Idiopathic Subcutaneous Thrombotic Vasculopathy - Godbe, Kerilyn; Elver, Ashlie; Chow, Peter; Williams, Chris; Fraga, Garth; Harris, Penelope; Taha, Mohammed; Bhavsar, Dhaval; Korentager, Richard (Frontiers in Medicine, 2022)
Lower extremity ulcers have significant morbidity, with treatment determined by the underlying disorder. Reported is a 32-year-old female presenting with small skin nodules and bruises across her legs four weeks following her second COVID vaccination. These lesions progressed into large, necrotic ulcers over several months. Initial work-up showed widespread pannicular thrombotic vasculopathy with ischemic skin necrosis. The tissue was negative for calcification on Von Kossa histochemistry, and a working diagnosis of subcutaneous thrombotic vasculopathy was suggested. The ulcers progressed despite treatments with corticosteroids, therapeutic anticoagulation, intravenous immunoglobulin, plasmapheresis, sodium thiosulfate, wound care, and repeat debridement. Later debridement specimens demonstrated rare vascular and pannicular calcifications. This finding supports the hypothesis that subcutaneous thrombotic vasculopathy is a precursor to calciphylaxis, the patient’s current working diagnosis. However, based on the patient’s entire clinical picture, a definitive diagnosis has yet to be found. This report highlights the challenges of working with rare diseases and the importance of multidisciplinary cooperation.